HUBUNGAN PELATIHAN DAN PENGAWASAN DENGAN AT RISK BEHAVIOR PADA PENGEMUDI MOBIL SAMPAH: Hubungan Pelatihan Dan Pengawasan Dengan At Risk Behavior Pada Pengemudi Mobil Sampah - Yetti Murni; Makomulamin Makomulamin; Buchari Lapau (Jurnal Kesehatan Komunitas, 2019)
At risk behavior of driver is an unsafety driving and it could harm themselves and others. One of the causes of the at risk behavior are lack of monitoring supervision, behavior of the industrial society as well as public community that haven't been optimal yet. It is 88% accident at work that caused by the unsafety behavior. This research aimed to find out the relation between knowledge, behavior, education, training, SOP and also the supervision of at Risk Behavior for dump truck's driver. This was an observational analytic quantitative study with cross sectional approach. The samples were 122 dump truck drivers. Data processing was done in the stages of editing, coding, entry, cleaning and tabulating. Data analyze was conducted by univariate, bivariate, and multivariate. The result showed that variables which has causality relation with at risk behavior, were the training (p=0,004) and the supervision (p=0,017). The confounding variable were the SOP and behavior while the education was not related to the variable. The conclusion was there is a causality relation between training and supervision with â€œAt Risk Behaviorâ€ of dump truckâ€™s driver. It is recommended for driver to participate in the training for work safety. It's also suggested for the supervisor to improving supervision method according to the policy and giving rewards to those drivers who's have great performance.